Etika Penggunaan Kecerdasan Buatan Dalam Dunia Pendidikan Islam - Gunagraha, Shindid; Chayati, Salim; Baidi, Baidi (Balai Diklat Keagamaan Bandung, 2025)
This research explores the application of artificial intelligence (AI) as a central theme in the educational setting, with a particular emphasis on its ethical implications. The purpose of this research is to identify and analyze ethical issues that arise due to the integration of AI in the learning process, as well as provide ethical recommendations in its implementation. This research uses a library research method by reviewing academic literature, research reports, and public policies related to AI and education. The results show that while AI provides significant benefits in terms of learning personalization, administrative efficiency, and educational accessibility, its use also poses serious ethical risks, such as violations of student data privacy, algorithmic bias, technology access gaps, and reduced social interaction in the teaching-learning process. In conclusion, the application of AI in education requires a strong ethical and regulatory framework to ensure fairness, transparency, and protection of the rights and dignity of students. Teachers continue to play an important role in overseeing the use of AI, ensuring that technology is a tool, not a substitute for human values in education.